Revisiting reflection in pre-service teacher training: let's rethink through a practicum in Spain. Issue 5 (2nd September 2020) - Saiz-Linares, Ángela; Susinos-Rada, Teresa
ABSTRACT: This article presents the findings of research in which a practicum programme based on a reflective and research-based teacher training approach has been designed, implemented, and evaluated. The purpose is to analyse the educational design and its ability to facilitate teacher training based on active and reflective learning. Methodologically, the research has the format of an evaluative case study. The data come from interviews, observations, and document analysis. The analysis reveals some key aspects, which explain the effectiveness of the proposal: 'pedagogical concerns' as activators of reflection, the complementarity of various reflective strategies, dialogical relationships, and the balance between planning and flexibility. The relevance of our work relates to the need to review the practical training of pre-service teachers in Spain, updating the principles towards reflective professionals and also to facilitate professional practice informed by research.